2008
DOI: 10.1017/s0022149x08006196
|View full text |Cite
|
Sign up to set email alerts
|

Anisakid parasites of the pouting (Trisopterus luscus) from the Cantabrian Sea coast, Bay of Biscay, Spain

Abstract: An epidemiological survey was undertaken of anisakids in 139 specimens (length: 13.2-24.5 cm) of pouting or bib (Trisopterus luscus) captured off the coast of northern Spain in the Cantabrian Sea. Third-stage larvae of two species of nematodes, Anisakis larvae type I and Hysterothylacium aduncum, were isolated. One adult female H. aduncum was also detected in the intestine of one pouting. Total prevalence of anisakids was 88.5%. Hysterothylacium aduncum and Anisakis showed, respectively, prevalence of 87.8% an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…H. aduncum also was found in Spain in S. pilchardus (Rello et al, 2008a;Sanmartín et al, 1994), E. encrasicolus (Rello et al, 2009), T. trachurus (MacKenzie et al, 2008;Sanmartín, Quinteiro, & Ubeira, 1989), species of fish for which this parasite was not found in the present study; H. aduncum was also found in Spain in M. poutassou (Fernández, Aznar, Montero, & Raga, 2005;Valero et al, 2000), Lepidorhombus whiffagionis, L. boscii and Microchirus variegates (Sanmartín et al, 1989;Álvarez et al, 2002), P. phycis and P. blennoides (Valero et al, 2006b) and Trisopterus luscus (Rello, Adroher, & Valero, 2008b) species of fish that were not studied in the present work.…”
Section: Site Speciesmentioning
confidence: 50%
“…H. aduncum also was found in Spain in S. pilchardus (Rello et al, 2008a;Sanmartín et al, 1994), E. encrasicolus (Rello et al, 2009), T. trachurus (MacKenzie et al, 2008;Sanmartín, Quinteiro, & Ubeira, 1989), species of fish for which this parasite was not found in the present study; H. aduncum was also found in Spain in M. poutassou (Fernández, Aznar, Montero, & Raga, 2005;Valero et al, 2000), Lepidorhombus whiffagionis, L. boscii and Microchirus variegates (Sanmartín et al, 1989;Álvarez et al, 2002), P. phycis and P. blennoides (Valero et al, 2006b) and Trisopterus luscus (Rello, Adroher, & Valero, 2008b) species of fish that were not studied in the present work.…”
Section: Site Speciesmentioning
confidence: 50%
“…Second, the growing popularity of eating raw or uncooked seafood may have resulted in the proliferation of this parasitic infection [5]. Third, there may be a higher parasitism/infestation of fish related to current fishing and aquaculture practices, which elevates risk of anisakidosis in consumers [18, 19].…”
Section: Discussionmentioning
confidence: 99%
“…This correlation was explained both by the accumulation of parasites during the life of the fish, considering the long life span of these parasites and by the ontogenetic shift in the feeding behavior of the fish, with the consumption of potentially more heavily infected prey by bigger fish. However, some authors found either no relationship between fish size and ascaridoid infection or a negative correlation, with the smallest fish heavily infected compared to the big ones (Horbowy et al, 2016;Rello et al, 2008;Strømnes and Andersen, 1998). These authors considered this to be the result either of an increasing mortality of large and heavily infected cod (due to a decrease of the fish condition and/or more intensive predation on these animals), or of an immune mechanism allowing the fish to eliminate the parasites (Levsen and Berland, 2011).…”
Section: Ascaridoid Nematodes and Fish Sizementioning
confidence: 99%